2020
DOI: 10.1103/physrevphyseducres.16.010124
|View full text |Cite
|
Sign up to set email alerts
|

Extending modified module analysis to include correct responses: Analysis of the Force Concept Inventory

Abstract: Brewe, Bruun, and Bearden first applied network analysis to understand patterns of incorrect conceptual physics reasoning in multiple-choice instruments introducing the Module Analysis for Multiple-Choice Responses (MAMCR) algorithm. Wells et al. proposed an extension to the algorithm which allowed the analysis of large datasets called Modified Module Analysis (MMA). This method analyzed the network structure of the correlation matrix of the responses to a multiple-choice instrument. Both MAMCR and MMA could o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…3(a), showed that many researchers considered the development of assessment to reveal students' understanding. Especially revealing students' understanding before implementing the learning process [1], [38]- [40].…”
Section: Methodsmentioning
confidence: 99%
“…3(a), showed that many researchers considered the development of assessment to reveal students' understanding. Especially revealing students' understanding before implementing the learning process [1], [38]- [40].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, an important consideration is how data from CIs and other measures are analyzed. Focusing only on correctness or measures of gain may limit researchers’ and instructors’ understanding of learning (e.g., the type and nature of incorrect answers students give reveals little about the various types of thinking that could have led to the answers; Brewe et al, 2016; Wallace & Bailey, 2010; Wells et al, 2019; Yang et al, 2020).…”
Section: Past Views On Active Learning and Its Measurementmentioning
confidence: 99%
“…An example is the "impetus" module found by Brewe et al, which is dominated by answers students could arrive at following a line of reasoning where a contact force (either constant or diminishing) continues to act on an object after contact has stopped. Recent work has expanded MAMCR to work with larger FCI data sets [19], applied this modified MAMCR to the FMCE [17], and extended it to include students' correct answers on the FCI [18].…”
Section: Introductionmentioning
confidence: 99%